The relationship between the position adopted by the baby during sleep and the prevention of sudden infant death (International Seven Journal of Health Research, 2024)
Introduction: Sudden Infant Death Syndrome (SIDS) is a term used to describe the sudden and unexpected death of an infant under 1 year of age, where the definitive cause of death cannot really be established, even after thorough investigation. The supine position is recommended by the American Academy of Pediatrics (AAP) as part of a safe sleep routine for babies. However, the prone position is contraindicated, as it is associated with a higher mortality rate. Method: The search for references was carried out on the Virtual Health Library (VHL) and Scielo platforms. The following descriptors were used: “Dorsal Decubitus” AND “Sudden Infant Death”. The following filters were applied: full-text article; main subject “Sudden Infant Death”; language in Portuguese, English and Spanish and publications in the last 5 years (2018-2023). This resulted in a total of 35 results, of which only 11 articles were selected. Results and Discussion: There are several modifiable factors related to sudden infant death, among them: caregivers of children who consume alcohol, tobacco and other drugs in the home during the prenatal and postnatal periods; bed sharing between babies and parents; overheating; presence of soft objects in the crib and loose bedding. Other important guidelines, which have a level A of evidence, for the prevention of SIDS are: exclusive breastfeeding; avoid exposure to cigarettes during and after pregnancy, as well as marijuana, opioids, alcohol and illicit drugs; carry out adequate prenatal care and the correct immunization recommended for the child and do not use home cardiorespiratory monitors. Aside from sleep, it is recommended to disseminate and educate children on safe sleep guidelines from the beginning of pregnancy, given that 40% of mothers say they have not received such guidance and 25% receive information that differs from that advised by the AAP. Conclusion: Sudden Infant Death Syndrome (SIDS) is related to the prone position. In the US, there are racial/ethnic disparities in SIDS mortality rates, associated with socioeconomic factors and lack of resources. It is crucial that public health services promote safe forms of sleep, such as the supine position, adequate feeding before sleep and the use of flat surfaces without objects in the crib.